If we want to apply the forward Euler method to x′′=x with x(0)=0,x′(0)=1, we can introduce a new function u:=[x′ x]

metodystap9

metodystap9

Open question

2022-08-13

If we want to apply the forward Euler method to x = x with x ( 0 ) = 0 , x ( 0 ) = 1, we can introduce a new function
u := [ x x ]
then
u = [ 0 1 1 0 ] u     and     u ( 0 ) = [ 1 0 ] .
So then first step of the forward Euler would be
u 1 = u ( 0 ) + h u ( 0 ) = [ 1 0 ] + h [ 0 1 1 0 ] [ 1 0 ] = [ 1 h ] .
And if we translate it back we get x 1 = h.
How can we do a similar thing with the equation x = x 2 (with x ( 0 ) = 0 , x ( 0 ) = 1)? It doesn't look like it can be written as a system, so there should be some other trick.

Answer & Explanation

Jazmyn Bean

Jazmyn Bean

Beginner2022-08-14Added 18 answers

Let u = [ x x ] . Then, u = [ x x ] = [ x x 2 ] with u ( 0 ) = [ 0 1 ] .
So, taking forward Euler steps yields:
u ( h ) u ( 0 ) + h u ( 0 ) = [ 0 1 ] + h [ 1 0 2 ] = [ h 1 ]
u ( 2 h ) u ( h ) + h u ( h ) = [ h 1 ] + h [ 1 h 2 ] = [ 2 h 1 + h 3 ]
u ( 3 h ) u ( 2 h ) + h u ( 2 h ) = [ 2 h 1 + h 3 ] + h [ 1 + h 3 ( 2 h ) 2 ] = [ 3 h + h 4 1 + 5 h 3 ]
and so on. The only difference is that u is a non-linear function of u.

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?